Une marque d’atelier sur une bouteille en verre découverte à Arles - Souen Fontaine; Nicolas Tran (Gallia)
A glass bottle bottom, discovered in the Rhône’s fluvial deposit, in Arelate (Arles), has a workshop mark on it, that can be linked with five already known signatures. It mentions the output of an officina run by someone named Titienus Iacinthus.